Plan de marketing para la comercialización de cinco hortalizas orgánicas de raíz, en el cantón Quevedo, año 2014 - González Montoya, Marco Antonio (2015)
The research aims to know the preferences of the five organic root vegetables, for creating the marketing plan marketing five organic root vegetables in the canton Quevedo, allowing project the marketing of this product in supermarkets and commissaries of the town, with the presentation of various organic root vegetables are carrots, radishes, beets, red onion white onion and providing the inhabitants welfare and health. Also through the application of research techniques and survey the market study to the economically active population of the canton Quevedo is of 74,995 inhabitants by 2014, with a sample corresponding to 383 surveys were conducted, the method was also used Inductive to determine the marketing of organic vegetables, obtaining results through surveys of people Quevedo Canton, organic vegetables currently identifies the markets for the food product market and have a better perspective of marketing venues, vegetables Organic ce do not have any strategy also lacks marketing products in markets and supermarkets in the town, indicating the lack of a marketing plan it affects sales and prevents people with knowledge of organic vegetables as indicating that 89% do not It has information about organic vegetables in the city of Quevedo, which is why we must make an emphasis on media best suited to the marketing of five organic root vegetables, since 99% of respondents who consume vegetables and 87% of respondents consider if they are willing to pay a higher price for organic vegetables. The above is the proposal for the commercialization of five organic root vegetables identifies strategies through marketing mix based on product, price, place and promotion-advertising.